Comparison Study of CBFs and EBFs Bracing in Steel Structures with Nonlinear Time History Analysis - Yaseer Khademi; Mehdi Rezaie (Salehan Institute of Higher Education, 2017)
Steel concentrically braced frames (CBFs) and Steel eccentricity braced frames (EBFs) are frequently used as efficient lateral load resisting systems to resist earthquake and wind loads. This paper focuses on high seismic applications where the brace members in CBFs and EBFs dissipate energy through repeated cycles of buckling and yielding. The present study evaluates in detail the design philosophies and provisions used in the United States for these systems. The results of a total of 176 analysis of nonlinear history of seismic behavior of CBFs and EBFs braces have been presented. Notable differences are observed between the performances of the CBFs and EBFs designed using American provisions. The similarities and differences are thoroughly discussed.